Clinical utility of haematological inflammatory biomarkers in predicting 30‐day mortality in hospitalised adult patients with COVID‐19. (21st November 2022) - Embaby, Ahmed; Hamed, Mohamed Gaber; Ebian, Huda; El‐Korashi, Lobna A.; Walaa, Mohammad; Abd el‐Sattar, Eman M.; Hanafy, Amr Shaaban; Abdelmoneem, Shimaa
Summary: Coronavirus disease 2019 (COVID‐19) is a multisystem disease affecting respiratory, cardiovascular, gastrointestinal, neurological, immunological and haematological systems. The most important indices that have been studied are platelet (PLT) indices in addition to the PLT count and red blood cell distribution width (RDW). This retrospective study included 95 patients with COVID‐19 and was conducted at the Hospital Isolation, Scientific and Medical Research Centre and Clinical Pathology Department at Zagazig University Hospitals, Egypt over 6 months from March to August 2021. All patients on admission had a full blood count, which included white blood cell (WBC) count, haemoglobin, RDW, PLT count and its indices in addition to PLT‐to‐WBC ratio (PWR) and PLT‐to‐lymphocyte ratio (PLR), which were calculated for all the study patients. There were significant linear correlations for higher levels of the PLR, PWR and RDW and mortality rate ( p  = 0.03, p  < 0.001 and p  < 0.001 respectively). Moreover, on multivariable analysis the RDW, PLT count and PWR levels were independent prognostic predictors for mortality with a hazard ratio [HR] of 1.25 (95% confidence interval [CI] 1.09–1.44, p  = 0.002), 1.00 (95% CI 0.99–1.00, p  = 0.03) and 2.3 (95% CI 1.21–4.48, p  = 0.01) respectively. The RDW and PLT indices are accessible predictors that can be valuable prognostic factors for survival assessment and risk stratification of COVID‐19.